Comparative Study of Autologous Peroneus Longus Versus Hamstring Tendon for Anterior Cruciate Ligament Reconstruction in Knee - Singh, Dr. Anurag; Krishnan, Dr. Rohan; Singh, Dr. Jaiveer (International Journal of Innovative Research in Medical Science, 2022)
Study Design: Prospective and Interventional Randomized Comparative Study. Duration of Study: October 2019 to September 2021. Objective: To compare the: 1) Functional outcome using IKDC score. 2) Donor site morbidity by AOFAS score and mid-thigh circumference between the autologous peroneus longus tendon and hamstrings tendon graft in ACL reconstruction. Methodology: Study was done on around 100 patients and patients were grouped under two categories. Gr A undergoing Autologus Peroneus Longus tendon and Gr B undergoing hamstrings tendon graft in ACL reconstruction. Both the group of patients were regularly followed up in Post op wk 1, wk 4. Wk 8 and outcomes were measured via AOFAS score and statistical analysis. Observation and Result: Based on our observation we conclude that both the groups were comparable in terms of post operative knee functional score and donor site morbidity. However, the ease of harvest due to its superficial location, short operative time, adequate graft thickness, absence of any muscle weakness and a relatively smaller post operative scar makes peroneus longus is a good alternative choice for anterior cruciate ligament reconstruction.